2009
DOI: 10.1590/s1677-54492009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Common celiacomesenteric trunk: a rare anatomic variation

Abstract: Common celiacomesenteric trunk, with the celiac and superior mesenteric arteries having a common origin from the aorta, is the least frequently reported anatomic variation of all abdominal vascular anomalies. Knowledge of variations concerning the celiac trunk and superior mesenteric artery are of great importance for both surgical approaches and angiographic examinations. Clinicians should keep in mind these variations to avoid complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…4 The incidence of CMT reported by other workers are given in Table 1 MDCT angiography. Origin of right or left inferior phrenic or common inferior phrenic trunk as an additional branch from celiac artery arising from CMT was reported by Bhatnagar et al 26 Sridhar Verma et al 27 reported the initial division of CMT into gastrosplenic and hepatomesenteric trunks and Kara et al 28 reported that the CMT after giving origin to CHA and SA continued as the gastromesenteric trunk which then split into LGA and SMA. It is observed that there is a male preponderance in the occurrence of CMT in the published case reports.…”
Section: Discussionmentioning
confidence: 86%
“…4 The incidence of CMT reported by other workers are given in Table 1 MDCT angiography. Origin of right or left inferior phrenic or common inferior phrenic trunk as an additional branch from celiac artery arising from CMT was reported by Bhatnagar et al 26 Sridhar Verma et al 27 reported the initial division of CMT into gastrosplenic and hepatomesenteric trunks and Kara et al 28 reported that the CMT after giving origin to CHA and SA continued as the gastromesenteric trunk which then split into LGA and SMA. It is observed that there is a male preponderance in the occurrence of CMT in the published case reports.…”
Section: Discussionmentioning
confidence: 86%
“…The study of superior mesenteric vessels is of great importance when pancreatic head carcinoma invades the superior mesenteric vein. Also, in depth knowledge of the anomalous branching pattern of SMA is essential for the successful accomplishment of the surgical, oncologic or interventional procedures because of the large visceral territory supplied by a single vessel [6].…”
Section: Resultsmentioning
confidence: 99%
“…The chance of compression of common celiacomesenteric trunk by the overlying large median arcuate ligament and the aortic opening are high because of its large size and position. So during the evaluation of coeliac trunk compression syndrome the existence of a common coeliacomesenteric trunk should be kept in mind [7]. Nayak et al reported a rare origin of the superior mesenteric artery and the common hepatic artery arising from the abdominal aorta as a common trunk and named as hepatomesenteric trunk.…”
Section: Discussionmentioning
confidence: 99%